Optimización utilizando lógica difusa de dispositivo de análisis de componentes químicos de ingredientes naturales basados en el internet de las cosas IoT - Angulo-Sogamoso, Karen Vanessa; Gil-Sierra, Danilo Gustavo; Salcedo-Parra, Octavio José (Revista Científica, 2017)
In the present article, the optimization is presented using diffuse logic of a device conformed by a scale with integrated sensors. These allow to identify the foods and to carry out a chemical analysis, in order to identify compounds that can be harmful to the health of the people. The bascule can be connected via Bluetooth to any mobile device, which, using an application programmed with the fuzzy logic technique, will allow the user a description of the components of any food, besides suggesting other ingredients that allow him to follow a Healthier and more balanced diet. The development methodology is divided into three stages, the first determining the characteristics of the scale, then the characteristics of the sensor and finally the development of the application. The implementation of the model is based on the correlation of an Expert System and Fuzzy Logic, where an inference system is established, considering the choice of input variables and the establishment of three macros that have integrated evaluations (Invima), Which will later allow the calculation of levels of toxicity in food. At the same time, in order to test and validate the model, in order to provide consistent results, we compare results obtained in other studies, where it can be shown that the model presented is more efficient in 7.57% with respect to the others are taken into consideration.